Analysis of single and multi-teller models using simulation for reducing waiting time: a case study of Access Bank and Eco Bank, Nig Ltd, in Taraba State Nigeria - Aideyan, D.O.; Ejiga, O.A. (International Journal of Mathematical Analysis and Modelling, 2023)
The essence of any organization is to solve problem and maximize its services and relevance among its subscribers and customers. In an attempt to actualize these, several practices are put in place depending on the type of services rendered and the type of subscribers. The banking sector tends to be one of the most customer oriented establishments in the private sector and thus infers a lot of carefulness in customer services and customer relations. One of the major factors influencing the success of organizations in today’s competitive world is to increase customer satisfaction through the improvement of service quality. In this research paper, it was observed that a customer is expected to come into the bank at every 0.72 minutes at Eco bank while at Access bank at every 0.46 minutes a customer comes in. It was also revealed that if it costs N400 (N 200 happiness cost and N 200 service cost) to attend to a customer the expected hourly cost of facility maintenance in Eco Bank is N 33,200 and for Access Bank is N 52,000 Thus at a single teller access bank spends a minimum cost of N 52, 0000 per hour to attend to 130 customers while at the multi teller, adopting the established average per teller; Eco Bank Spends for 4 tellers, N132,000 per hour attending to an average of 83 customers and Access bank spends for 6 tellers, N 312,000 per hour attending to an average of 130 customers. Thus, the cost of facility is dependent on the number of tellers and cost of internet service plus happiness service provided. In addition, the group descriptive statistics, though with varying distribution and sample selection between the banks due to validity of responses collected, there is a mean correlation and deviation in the assessment of empathy and reliability of teller system at both Eco Bank Nigeria and Access Bank Plc. With a related, mean mark above 2.5 and deviation below 0 and significant at 0.125 points to positive autocorrelation. On the other hand, the reliability mean marks are related at 3.148 and 3.528 with a mean deviation of 0.863 and 0.559 respectively. Assurance on its own has a lesser mean mark at 2.815 for Eco bank and 3.111 at Access bank. The deviations are similar at 0.786, which infers no significant difference by mere inspection. Finally, responsiveness as a proxy to measure performance the mean at 2.333 for EcoBank and Access bank at 2.639 this is quite poor and low thus, we could infer that at both Ecobank and Access bank the responsiveness of the tellers though reliable and assuring is low in responsiveness.